Analysis of Dieting with Gastritis in The Students of Muhammadiyah University Jakarta 2021 - Niesa Surya Dianti Putri; Alvira Rizka Utami; Amelia Novita; Cindi Maduri; Munaya Fauziah (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Gastritis is an inflammatory process or health problem caused by irritation and infection of the gastric mucosa and submucosa. Gastritis can attack all levels of society from all levels of age and gender. Diet is to provide an overview of the way or behavior taken by a person or group of people in choosing and using the food consumed every day which includes the regularity of eating frequency, meal portions, and the type of food and drink consumed based on social and cultural factors in which they live. According to Riskesdas 2013, the incidence of gastritis in several regions of Indonesia is quite high with a prevalence of 274,369 cases from 238,452,952 inhabitants, it was found that in the city of Surabaya the incidence of gastritis was 31.2%, Denpasar 46% while in Central Java the incidence of gastritis is quite high at 79.6%. Gastritis usually occurs due to irregular eating frequency so that the stomach becomes sensitive when stomach acid increases. It is better for people who have a history of gastric disease not to eat acidic and spicy foods because they can cause gastritis to recur.